A Study on Power Requirement in Thickness Planing - Rawat, B. S.; Rajput, S. S.; Pant, B. C. (Indian Forester, 1973)
Briefly surveying the work done on the problems of planing of timber, the various relationships between power requirement and variables of planing and strength characteristics of timber have been worked out on the basis of a study done of sixteen species. The relationships between cutter marks frequency-a characteristics often taken as quality index in planing-and feed speed have also been given for various standard type of planing machines manufactured in India.